Wound healing strategies - hyaluronic acid (HA) and chitosan (CS) as wound dressing materials - Nascimento, Adriana Batista (2020)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2020, Universidade de Lisboa, Faculdade de Farmácia.